2009
DOI: 10.1002/ar.20926
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fasting at Different Stages of Lighting Regimen on the Proliferation of Jejunal Epithelial Cells During Rat Pup Weaning

Abstract: The lifespan of intestinal epithelial cells is predetermined by the process of cell proliferation that occurs constantly in the crypt. The control of this process involves some endogenous factors, such as hormones, as well as exogenous factors, like food and natural light variations. These last two exogenous factors seem to be the major modulators of the cell proliferation process. Fasting treatment was conducted to assess the role of food and its effect on the metaphase index (MI) of the intestinal epithelium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In a previous study, which evaluated the morphometric changes in the small intestine of nursing piglets caused by 60% restriction, it was stated that this restriction resulted in a significantly reduced thickness of the mucosa and villus height compared with the control group ( 21 ). In other studies it was revealed that starvation induces proximal small intestine intestinal epithelial atrophy ( 22 , 23 ), which is more closely associated with increased epithelial cell apoptosis ( 24 ) than with the full process of cell proliferation in the crypts ( 25 ) and is the main cause of increased mucosal permeability ( 26 ). In the present study, which was oriented on the histological aspects of feed restriction, no pathological changes were observed.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, which evaluated the morphometric changes in the small intestine of nursing piglets caused by 60% restriction, it was stated that this restriction resulted in a significantly reduced thickness of the mucosa and villus height compared with the control group ( 21 ). In other studies it was revealed that starvation induces proximal small intestine intestinal epithelial atrophy ( 22 , 23 ), which is more closely associated with increased epithelial cell apoptosis ( 24 ) than with the full process of cell proliferation in the crypts ( 25 ) and is the main cause of increased mucosal permeability ( 26 ). In the present study, which was oriented on the histological aspects of feed restriction, no pathological changes were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it also acts as a barrier between the internal and external environments (De Mey & Freund, 2013). However, during all developmental stages, the organ is influenced by external factors, mainly light and food (Soares, Okada, Ayub, & Gomes, 2009). In mammals, the first food intake after birth is milk.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, small intestine also acts as a barrier between the body internal and external environment (De Mey and Freund, 2013). However, during all phases of development, the small intestine is under influence of the external factors, mainly light and the food (Soares et al, 2009). In mammalian, the first food intake after birth is milk.…”
Section: Discussionmentioning
confidence: 99%